IMAGE POLICY AS AN IMPORTANT FACTOR IN THE IMPROVEMENT AND PROGRESS OF THE COUNTRY - Bektosh Berdiev (Web of Journals Publishing, 2023)
The paper looks at the state’s internal and external image and the definitions of “concept” and “image” are clarified. The issues under discussion include the state image components, specifics of image building, specifics of country’s image on the domestic and foreign markets, and the PR goals in the building of state’s image.
Keywords: image, concept, state, corporation, formation, public relations.